2012
DOI: 10.5120/7647-0737
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ?-Glucan Production from Lower Fungi using Central Composite Design and its Biological Application

Abstract: Production of β-glucan is mainly used for cancer therapy. The most well-known are those occur in fungal grains such as cereal and other micro-organisms. The most important beta glucan from a nutritional and ingredient standpoint is that derived from fungal grain. Optimization of medium ingredients for the production of mycelial β-glucan from lower fungi in submerged fermentation and antioxidant activity of β-glucan was carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…The commonly used yeast S. cerevisiae can produce a β-glucan yield of about 6–12% ( Zechner-Krpan et al, 2010 ). A. niger can produce a yield of 9–11% ( Paulraj et al, 2012 ). In a recent approach, a maximum fungal biomass of 0.76 mg/g with β-glucan at 9.34% (w/w) was obtained during solid-state fermentation of brown rice by A. oryzae KCCM 12698 ( Ji and Ra, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The commonly used yeast S. cerevisiae can produce a β-glucan yield of about 6–12% ( Zechner-Krpan et al, 2010 ). A. niger can produce a yield of 9–11% ( Paulraj et al, 2012 ). In a recent approach, a maximum fungal biomass of 0.76 mg/g with β-glucan at 9.34% (w/w) was obtained during solid-state fermentation of brown rice by A. oryzae KCCM 12698 ( Ji and Ra, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moulds belonging to the genus Aspergillus can be used for β-glucan production ( Odabasi et al 2006 ). Paulraj et al (2012) obtained a dry weight of 0.78 g of A. niger mycelia and a dry weight of 0.5 g of β-glucan. Another species of Aspergillus that can be used for β-glucan production is A. oryzae .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has demonstrated that an increase in β-glucan concentration increases the antioxidant activity at a maximum of 78.31% at 100 µg/ml of concentration. This value is higher than that of ascorbic acid which resulted in a maximum of 51.80% radical scavenging activity at the same concentration (Paulraj and Saravanan, 2012).…”
Section: Antioxidant Propertiesmentioning
confidence: 94%